Implementation of Audio Visual Learning Media in Extracurricular Dance Activities - Nadiya, Nursya Fathin; Herpratiwi, Herpratiwi; Fitri, Dina Martha (UNDIKMA, 2025)
: The implementation of audio-visual media has an important role in extracurricular activities, especially in learning that prioritizes aspects of skills and practical activities such as in extracurricular dance activities. Audio visual media can display visuals clearly and audio simultaneously so that learning becomes more real. This study aims to analyze the implementation of audio-visual learning media that can be used in extracurricular dance activities. The research method used is literature study research by collecting data from various references such as books, journals and theses, then analyzing it, then reducing the data, presenting the data in matrix form and drawing conclusions. The results of the research that has been conducted are the importance of implementing audio-visual media learning in extracurricular dance activities which include planning, implementation, and evaluation because audio-visual media in extracurricular dance activities can provide more real experience to students, besides that extracurricular dance becomes more fun, varied, not monotonous, not boring, and students are not easily bored in learning. Judging from the appreciation shown through dance video shows, students absorb more knowledge about various kinds of dances. The conclusion of the research conducted is that audio visual media provides significant benefits, both for students and teachers. especially in dance skills material because audio visual media can attract students' interest and motivation, can stimulate thoughts, feelings, can attract students' attention and affect students' emotions so that dance learning becomes more fun, varied and not monotonous.